The effectiveness of hybrid project-based learning model in improving primary teacher education students’ critical thinking and creative thinking skills - Ahmad Ipmawan Kharisma; A.F. Suryaning Ati MZ; Alda Dwin Mar Elisah; inta Zahirah 4 Fillah; Wiwid Widiyanti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the effectiveness of the hybrid project-based learning model to improve students’ critical thinking and creative thinking skills. The research is quantitative research with a pretest-posttest control group design. The subjects involved elementary school teacher education students in the second semester of the academic year 2022/2023 at Universitas Muhammadiyah Lamongan. The research can be applied to students during the learning process. The measured research data were validity, practicality, and effectiveness of the research instrument. The results indicate that (a) the result of validity testing of the developed hybrid project-based learning model was very valid with a percentage of 94%. In addition, (b) the questionnaire analysis result of students’ responses in the experimental class was very good with a percentage of 94% while the result in the control class was 69% in the unfavorable category. Moreover, (c) the t-test analysis 0.023 < 0.05 with the N-Gain test results was 79.20%, which means that there was a significant difference and an increase in students’ critical thinking skills. And (d) the t-test analysis 0.019 <0.05 with the N-Gain test results was 77.11%, which means that there was a significant difference and an increase in students’ creative thinking skills. In conclusion, the hybrid project based learning model is feasible to use and can improve students’ critical thinking and creative thinking skills.